The effect of workload and work environment on employee turnover intention mediated by job satisfaction - Pahlawan, Ardhiansyah Fitria Sukma; Wahyuni, Purbudi (Universitas Sebelas Maret, 2022)
This study aims to analyze the effect of workload and work environment on turnover intention with the mediating variable of job satisfaction. This study uses a quantitative approach. Data and information were collected through a questionnaire survey using a gform. The population in this study are employees working at PT. Madhani Talatah Nusantara Jobsite 060 C in District Gunung Tabur, Berau Regency, East Kalimantan. Total is 943 employees. The sampling technique used is Cluster Random Sampling (Random sampling technique based on area or work cluster). The sample to be taken from a population of 943 with a staff of 199 people will be used as the object of research if, with an error of 10%, it is necessary to 133 respondents actual respondents 102. The analytical method used in this study is Structural Equation Modeling (SEM). The study's results indicate that the workload and work environment have a positive and significant direct effect on turnover intention. The workload is proven to impact turnover intention, which is remediated by job satisfaction. The work environment influences turnover intention, which is mediated by job satisfaction.